Kandungan Unsur Natrium, Sulfat dan Klorid pada Aplikasi Sludge Industri Lysine ke Tanah - Lutfi, Musthofa (Jurnal Teknologi Pertanian, 2001)
Methods of application of Lysine industrial sludge produced by Cheil Samsung Indonesia tosoil and the status of sodium, sulphate and chloride from the sludge upon application to the soilwere studied in the glasshouse.  Treatments carried out for the experiments were methodcombinations of sludge application (surface placed, incorporated and buried) and rate of sludgeapplication (25%, 50% and 75% weight/weight).  The nine treatments and one control soil (noapplication of sludge) were arranged in a randomized complete design with three replicates. The glasshouse experiment was aimed at studying the effect of methods and rate of sludgeapplication on changes in chemical properties of sludge with the presence of plant.  Theexperiments were carried out simultaneously for 60 days. The variables observed in glasshouseexperiment were the amount of sodium, sulphate and chloride available in sludge and therespective amount taken up by the corn on the 30th and 60th day.  Dry weight of shoot and root ofthe corn were also measured.   Result of the study showed that after 60 days of treatment the amount of sulphate and chloridein sludge decreased considerably, whereas the amount of sodium was relatively constant. Theuptake of sulphate and sodium by corn, dry weight of shoot and root of the corn were differentamong treatments.  There was, however, no difference in the amount of chloride taken up by corn.Keywords: lysine industrial, sludge application